2020
DOI: 10.5194/essd-12-935-2020
|View full text |Cite
|
Sign up to set email alerts
|

In situ airborne measurements of atmospheric and sea surface parameters related to offshore wind parks in the German Bight

Abstract: Abstract. Between 6 September 2016 and 15 October 2017, meteorological measurement flights were conducted above the German Bight in the framework of the project WIPAFF (Wind Park Far Field). The scope of the measurements was to study long-range wakes with an extent larger than 10 km behind entire wind parks, and to investigate the interaction of wind parks and the marine atmospheric boundary layer. The research aircraft Dornier 128 of the Technische Universität (TU) Braunschweig performed in total 41 measureme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…This result disagrees with the findings by Grashorn and Stanev (2016) and Rivier et al (2016), who reported increased turbidity caused by OWF foundations. Lampert et al (2020) provide airborne observations of a large-scale regional reduction in wind stress downwind of the OWF in the German Bight, confirming results of previous studies (e.g., Djath et al, 2018;Djath and Schulz-Stellenfleth, 2019;Cañadillas et al, 2020;Siedersleben et al, 2020). Consistent with the observations by Lampert et al (2020), atmospheric model simulations by Siedersleben (2019) show a reduction of wind speed by 5%-25% inside the wind wake 5 km downwind of a wind farm.…”
Section: Effects Of Wind Turbines On the Wind Fieldsupporting
confidence: 88%
“…This result disagrees with the findings by Grashorn and Stanev (2016) and Rivier et al (2016), who reported increased turbidity caused by OWF foundations. Lampert et al (2020) provide airborne observations of a large-scale regional reduction in wind stress downwind of the OWF in the German Bight, confirming results of previous studies (e.g., Djath et al, 2018;Djath and Schulz-Stellenfleth, 2019;Cañadillas et al, 2020;Siedersleben et al, 2020). Consistent with the observations by Lampert et al (2020), atmospheric model simulations by Siedersleben (2019) show a reduction of wind speed by 5%-25% inside the wind wake 5 km downwind of a wind farm.…”
Section: Effects Of Wind Turbines On the Wind Fieldsupporting
confidence: 88%
“…It is equipped among others with sensors for temperature, humidity, pressure, and wind components, sampling with a frequency of 100 Hz. Details about the measurement devices can be found in Corsmeier et al 24 and Lampert et al 25 The airspeed of the aircraft during the measurements flights was 66 m s −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The Flight No. is according to the total numbering of all flights during the WIPAFF campaigns in 2016 and 2017 7,25 . Thermal stability represents the atmospheric stratification.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Bundesnetzagentur (2019) for most German wind farms and (2) Energistyrelsen (2020) for Danish wind farms; (3) for other wind farms not included in these two datasets, turbine locations have been derived from SAR images in Langor (2019) and manually corrected to fit the wind farm shapes and turbine numbers from EMODnet (Emodnet, 2020). For the simulations in this study, only wind farms built before 2018 are included in accordance with the measurement time (Table 4).…”
Section: Modelingmentioning
confidence: 99%
“…The Senvion 6.2M126 turbine in the Nordsee One, OWP Nordergründe and OWP Nordsee Ost were similarly scaled from the DTU 10 MW reference turbine. Other power and thrust curves have been taken from Langor (2019) or from WAsP (http://www.wasp.dk/, last access: 29 May 2021). In Table 4 the wind farms are listed with the turbine model used in the simulations.…”
Section: Modelingmentioning
confidence: 99%